2006
DOI: 10.1149/1.2163788
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and In Situ XAFS-XRD Investigation of Nb[sub 2]O[sub 5] for Rechargeable Lithium Batteries

Abstract: Nb 2 O 5 exhibits various crystal systems, such as orthorhombic ͑o͒, tetragonal ͑t͒, and monoclinic ͑m͒, among which Nb 2 O 5 synthesized at 900-1000°C is commercially used as a cathode material of the 2-V lithium ion battery. The battery performances depended on the structure of Nb 2 O 5 , and the t-Nb 2 O 5 synthesized at 1000°C exhibited an excellent cycling performance with a large discharge capacity of 190 mAh ͑g oxide͒ −1 . The structural variations of Nb 2 O 5 during electrochemical reaction were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
159
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(169 citation statements)
references
References 21 publications
(20 reference statements)
9
159
1
Order By: Relevance
“…The increase in impedance with continued cycling suggests that some reaction between LLZNO and Li electrodes had occurred. It is known that Nb 5+ can be reduced to Nb 4+ at relatively low potentials (Kodama et al, 2006;Wang et al, 2011). Therefore, the reduction of Nb 5+ may adversely affect charge transport in LLZNO and/or the formation of a passivating layer.…”
Section: Cycling and Electrochemical Impedancementioning
confidence: 99%
“…The increase in impedance with continued cycling suggests that some reaction between LLZNO and Li electrodes had occurred. It is known that Nb 5+ can be reduced to Nb 4+ at relatively low potentials (Kodama et al, 2006;Wang et al, 2011). Therefore, the reduction of Nb 5+ may adversely affect charge transport in LLZNO and/or the formation of a passivating layer.…”
Section: Cycling and Electrochemical Impedancementioning
confidence: 99%
“…Nb 2 O 5 could find applications in low voltage (2 V range) applications such as microelectronic or memory back up [2] systems. Different polymorphs of Nb 2 O 5 compounds that have been studied are pseudo-hexagonal (H), orthorhombic (O), tetragonal (T), and monoclinic (M) [2,3]. Kodama et al [3] found that O-Nb 2 O 5 particles possess superior cycling performance compared to M-Nb 2 O 5 particles.…”
Section: Introductionmentioning
confidence: 99%
“…Different polymorphs of Nb 2 O 5 compounds that have been studied are pseudo-hexagonal (H), orthorhombic (O), tetragonal (T), and monoclinic (M) [2,3]. Kodama et al [3] found that O-Nb 2 O 5 particles possess superior cycling performance compared to M-Nb 2 O 5 particles. In our previous work, we made an opposite observation in the case of bare and Ta-doped Nb 2 O 5 nanofibers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 However, the kinetics of this material had never been determined. The results with mesoporous films indicated that not only that Li + insertion was extremely rapid but also that mesoporous crystalline materials (orthorhombic T-phase) had much better kinetics and charge storage properties than the corresponding mesoporous amorphous films.…”
Section: Capacitive Energy Storagementioning
confidence: 99%